2023
DOI: 10.3390/su15043219
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Behavioral Intention in Eco-Friendly Hotels? The Roles of Tourist’s Perceived Value and Satisfaction: A Case Study of Thailand

Abstract: Currently, the hospitality industry is related to environmental issues, generating both positive and negative impacts for the earth. Tourists are interested in staying and spending money in hotels that care about the environment. Based on the previous research in the hotel industry, empirical studies showed a relationship between perceived value and tourist satisfaction in general. Consequentially, this study aimed to empirically investigate the relationship between eco-friendly perceived value (EFPV), tourist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…Van Huy et al [14] concluded that visitor satisfaction significantly influences their intention to revisit eco-friendly hotels. Similarly, Kokkhangplu et al [40] also found that visitors' satisfaction plays a crucial role in influencing their intention to visit eco-friendly hotels. However, this study delves deeper into understanding how visitors' satisfaction translates into outcomes such as revisit intention (RVI), word-ofmouth influence (WOMI), and willingness to pay a premium (WTPP).…”
Section: Theoretical Implicationmentioning
confidence: 94%
See 3 more Smart Citations
“…Van Huy et al [14] concluded that visitor satisfaction significantly influences their intention to revisit eco-friendly hotels. Similarly, Kokkhangplu et al [40] also found that visitors' satisfaction plays a crucial role in influencing their intention to visit eco-friendly hotels. However, this study delves deeper into understanding how visitors' satisfaction translates into outcomes such as revisit intention (RVI), word-ofmouth influence (WOMI), and willingness to pay a premium (WTPP).…”
Section: Theoretical Implicationmentioning
confidence: 94%
“…Furthermore, Park and Kang [38] found that customers' green perceptions and their feelings toward eco-friendly artwork influence their intention to visit eco-friendly hotels. Noticeably, the majority of previous studies have mainly focused on foreign visitors or both local and foreign visitors [39,40]. Table 1 below provides an overview of several pertinent prior studies falling within the scope of this study.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found the CS mediation effect of SQ on BI [12,13]. There are also studies that confirm that CS mediates the effect of PV on BI [13][14][15]. The literature focusing on the contribution of IC B&B SQ to the interpretation of BI is sparse, and research on IC B&B is still in its infancy [16].…”
Section: Introductionmentioning
confidence: 99%